2022
DOI: 10.3390/ijerph192013092
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics and Kinetics Insights into Fluoride Removal from Drinking Water Using Magnetic Tea Biochar

Abstract: Fluoride contamination in water is a key problem facing the world, leading to health problems such as dental and skeletal fluorosis. So, we used low-cost multifunctional tea biochar (TBC) and magnetic tea biochar (MTBC) prepared by facile one-step pyrolysis of waste tea leaves. The TBC and MTBC were characterized by XRD, SEM, FTIR, and VSM. Both TBC and MTBC contain high carbon contents of 63.45 and 63.75%, respectively. The surface area of MTBC (115.65 m2/g) was higher than TBC (81.64 m2/g). The modified bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Further, the statistical error and chi-square calculations (Table S2 ) found that Freundlich's model fitting shows a low chi-square value. These results suggest that each adsorption site on the KOH-SSAC surface possesses distinct adsorption energies and affinities for phenol and BPA 41 .…”
Section: Resultsmentioning
confidence: 82%
“…Further, the statistical error and chi-square calculations (Table S2 ) found that Freundlich's model fitting shows a low chi-square value. These results suggest that each adsorption site on the KOH-SSAC surface possesses distinct adsorption energies and affinities for phenol and BPA 41 .…”
Section: Resultsmentioning
confidence: 82%
“…Figure 11 shows the FTIR spectra of TBC, La-TBC, and La-TBC-F. Among these, the characteristic peaks of the three biochar materials that appeared at wave number 3442 cm −1 were mainly due to the O-H stretching vibration in the H 2 O on the surface of the materials [40]; the characteristic peaks appearing at wave number of 1628 cm −1 were caused by the vibration of C=O and C=C, which indicates that the carbon composition of the materials was complex [41]; the characteristic peaks appearing at 1384 cm −1 were caused by the vibration of −NO 3 , and the intensity of the characteristic peaks was increased after modification, which implies the presence of nitric oxides, such as nitrate, in the materials [42]. Comparing the TBC spectra, we see that those for La-TBC showed new characteristic absorption peaks at wave numbers of 1493 versus 1042 cm −1 , which can be attributed to the reaction of La(OH) 3 with the CO 2 in air to form carbonate groups [43], and the peak at 739 cm −1 can be attributed to the La-OH vibration [32], indicating that lanthanum (La) has been successfully loaded.…”
Section: Ftir Analysismentioning
confidence: 98%
“…Various low-cost, high-efficiency, and environmentally friendly methods are emerging techniques used to treat water for drinking purposes, specifically focusing on their relevance in developing countries. For example, Ashraf et al [8] proposed a renewable technique using magnetic tea biochar as a means to remove fluoride from water and ensure its suitability for drinking. Other studies conducted by Teng and Altaf [9,10] focused on the removal of highly persistent mercury from water to ensure safe drinking water and protect human health using eco-friendly techniques.…”
Section: Introductionmentioning
confidence: 99%